Piękno was wyzwoli. Sztuka według Nietzschego według Heideggera .......... 9 - Łojek , Stanisław (Na Przełomie: 25 lat seminarium filozoficznego. Uniwersytet Jagielloński 1995-2020, 2020)
BEAUTY WILL FREE YOU. NIETZSCHE’S UNDERSTANDING OF ART ACCORDING TO HEIDEGGEHeidegger often creatively interpreted Nietzsche’s thought, and he was doing this, among other things, in order to give better expression to what he himself had to say. That would not be possible, however, if both philosophies didn’t have certain affinity. This is perhaps most evident in the Heideggerian interpretation of the Nietzschean view of the will to power as art. It shows that both thinkers recognize the metaphysical meaning of art and give it a distinctive place within the whole of reality.For Heidegger, Nietzsche is also the thinker who recognized nihilism and pointed to its source in previous metaphysics, thus revealing the necessity of overcoming it. He holds Nietzsche’s thought to be a penetrating diagnosis of the condition of our times, which Heidegger himself described as the era of fulfilled meaningless, a diagnosis that also reveals the need and the ways of its transgression.Nietzsche dared to say that the world can be justified only as aesthetic phenomenon, that in the moral interpretation of the world, underlying the whole of our metaphysical tradition, this world is denigrated and denied. Hence, for him art had more worth than (metaphysically understood and always much more valued) truth. In The origin of the work of art, Heidegger also examines the relationship between art and truth, and describes the work of art in such a way as to show that the truth of being reveals itself in it. And it is this disclosure that, in his opinion, constitutes the essence of art. Thus, Nietzsche’s teaching about the will to power as art allowed Heidegger to expose and clarify the issues that were beginning to define his own thought. Nietzsche thought that art is capable of overcoming nihilism, claiming at the same time that in order for it to fulfil this task, it must be understood and practiced quite differently than so far. But according to Heidegger, Nietzsche’s “reversal” of tradition has turned out to be, contrary to the intentions of its author, its crowning and completion. Remaining within tradition, and radicalising it, Nietzsche understood art in a wrong way. Thus, precisely because Heidegger agrees with Nietzsche that turning art against nihilism requires a break with its current understanding, he does not adhere to Nietzsche’s solution and insists on a different approach to art.According to Heidegger, Nietzsche was able to recognize that all metaphysics, all Western tradition, was fundamentally nihilistic and experience nihilism on its own, because his own thinking was nihilistic as well. And it was this entanglement that made him unable to recognize the proper essence of nihilism. His quarrel (Auseinandersetzung) with Nietzsche, however, could not end there. Heidegger also saw his thought as an impulse for a new beginning. He decided to really do what Nietzsche intended to do: overcome metaphysics and leave nihilism behind. Nietzsche could not do this because, hopelessly entangled in tradition, he was unable to recognize the real metaphysical basis of nihilism. And this, according to Heidegger, consists in the forgetfulness of being; oblivion that results in forgetting the essence of both truth and art, and thus condemns them to remain in a dissonance.When being is forgotten, truth ceases to reveal itself in things and is transferred beyond them, as an external measure of their truth or reality. And because we impose such an external measure on things whenever we encounter them, they cannot reveal to us what and how they are in themselves. Heidegger and Nietzsche agree that depriving things of their own truth is nihilism. And they both think that it is by art that nihilism might be overcome. Because art, they believe, is a very special domain of being in which and through which whatever is reveals itself most fully and clearly.